CALCULATION OF OIL PALM HARVESTER PREMIUM BASED ON SLOPE CLASS BASED ON GEOGRAPHIC INFORMATION SYSTEM IN SEI SILAU PLANTATION PT.PERKEBUNAN NUSANTARA III (PERSERO) - Jeremia Hutauruk; E. Harso Kardhinata; Ihsan Effendi (CV. Radja Publika, 2024)
PT Perkebunan Nusantara III is a state-owned company engaged in plantation activities. Sei Silau Plantation is one of the units that manages oil palm plantations. One of the factors that determines the company's performance is the productivity of the harvesters. The amount of premium received by harvesters is a factor that affects motivation and performance, but the determination of premiums still uses general slope data for each harvest area in determining the task base. The method used in this research is spatial data processing, overlaying slope data from Demnas with regional boundaries at each level and then analysing the increase in productivity and premiums. The results showed that the slope class from the spatial analysis was divided into three parts, namely flat and undulating (0-15%) covering 114.91 ha/45.85%, hilly (15-45%) covering 110.34 ha/44.03% and hilly without terraces (>45%) covering 25.35 ha/10.12% of the total oil palm area. The slope class of each plantation is divided into three classes. There was an increase in productivity and premium after the method change, namely an increase in productivity from April to May by 214.95 kg/17.04%, May to June by 123.43/8.43% and April to June by 339.38 kg/26.90%, and an increase in premium from April to May by Rp 3,190,252/22.20%, May to June by Rp 1,642,123/9.35% and April to June by Rp 4,832,375/33.63%. This shows a clear correlation between increased productivity and increased premiums.